Therapeutic advances in metastatic pancreatic cancer: a focus on targeted therapies. (September 2022) - Turpin, Anthony; Neuzillet, Cindy; Colle, Elise; Dusetti, Nelson; Nicolle, Rémy; Cros, Jérôme; de Mestier, Louis; Bachet, Jean-Baptiste; Hammel, Pascal
Mortality from pancreatic ductal adenocarcinoma (PDAC) is increasing worldwide and effective new treatments are urgently needed. The current treatment of metastatic PDAC in fit patients is based on two chemotherapy combinations (FOLFIRINOX and gemcitabine plus nab-paclitaxel) which were validated more than 8 years ago. Although almost all treatments targeting specific molecular alterations have failed so far when administered to unselected patients, encouraging results were observed in the small subpopulations of patients with germline BRCA 1/2 mutations, and somatic gene fusions ( neurotrophic tyrosine receptor kinase, Neuregulin 1, which are enriched in KRAS wild-type PDAC), KRAS G12C mutations, or microsatellite instability. While targeted tumor metabolism therapies and immunotherapy have been disappointing, they are still under investigation in combination with other drugs. Optimizing pharmacokinetics and adapting available chemotherapies based on molecular signatures are other promising avenues of research. This review evaluates the current expectations and limits of available treatments and analyses the existing trials. A permanent search for actionable vulnerabilities in PDAC tumor cells and microenvironments will probably result in a more personalized therapeutic approach, keeping in mind that supportive care must also play a major role if real clinical efficacy is to be achieved in these patients.